The Englightenment, please! - Mercedes Rosúa (FahrenHouse, 2009)
The Movement of the Enlightenment, the ideals that gave life to it, the universal humanist values that it sought to spread, the defense of Lights of Intelligence and Reason are, here and now, much necessary. They are, however, in a very serious danger. It is being a big ef- fort aimed to eradicate these values from culture and consciences. The attack against the spirit of the Enlightenment is part of a wider movement of socio-politic manipulation, voluntary blindness in the face of evidence and refuse of facts, data and logic. Education has been one of the main victims of this process. The present system, set up by the socialist party, hinders the acquisition of basic knowledge, deters or minimizes essential subjects, blames effort, individual work and merit and promotes narrow-mindedness, medio- crity and ignorance. The rising -with the welfare estates- of a class of people living on subsidized Utopia has been a specific fact of modern times. Spain is particularly vulnerable because a quite important part of mass media and politicians is a parasite one who, after the Transicion (transi- tional period to democracy) and since then, takes advantage of after-Franco's blackmail in order to impose a dual creed and to get the ethical monopoly. There is in Spain a huge quantity of those living on myths, slogans and victimization, just made to justify the ownership of money, state, status and power. In this way, the manipulation of History and present has been, in and out the country, extremely important, with no report, neither denunciation, on the obvious edu- cational, cultural and, during those last years, economic disaster. The ideas aimed to the excellence have been the first cause that took away human beings from barbarism; these ideas have built free and successful societies. Now more than ever, when we face ignorance, irrationality, confused multiculturalism and relativity of values, the Enligh- tenment is needed.